2009
DOI: 10.4067/s0716-078x2009000200010
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of Egeria densa Planchón (Liliopsida: Alismatales): A wetland ecosystem engineer?

Abstract: Egeria densa Planchon is considered an invasive species in continental aquatic systems in Chile. Its original geographical distribution was limited to the subtropical regions of Brazil, Argentina and Uruguay. Its fast growth and dense canopy-forming habit are associated with the clear water state of shallow water continental ecosystems. As a dominant species in many of the systems in which it occurs, E. densa behaves as an ecosystem engineer by preventing the re-suspension of sediments and controlling the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 59 publications
(24 reference statements)
4
107
0
5
Order By: Relevance
“…In order to assess the SAV classification accuracy for the other images (i.e., 2013, 2015, and 2016), we identified total 17 SAV stations used for validation (i.e., Station 1,5,6,9,15,18,27,34,36,38,41,42,43,45,48, 49 and 52) out of 52 observation points (Figure 1) based on the available data in Table 1 and the in situ survey (2016). We also used the SAV biomass maps available in the literature for the south basin of Lake Biwa, primarily for the SAV growth period (i.e., mainly September) in 2002, 2007, 2012, and 2014 [63,65].…”
Section: Sav Distribution Mapmentioning
confidence: 99%
“…In order to assess the SAV classification accuracy for the other images (i.e., 2013, 2015, and 2016), we identified total 17 SAV stations used for validation (i.e., Station 1,5,6,9,15,18,27,34,36,38,41,42,43,45,48, 49 and 52) out of 52 observation points (Figure 1) based on the available data in Table 1 and the in situ survey (2016). We also used the SAV biomass maps available in the literature for the south basin of Lake Biwa, primarily for the SAV growth period (i.e., mainly September) in 2002, 2007, 2012, and 2014 [63,65].…”
Section: Sav Distribution Mapmentioning
confidence: 99%
“…(Jacoby et al 2000;Lehman et al 2005Lehman et al , 2008 and the establishment of nuisance aquatic vegetation (largely E. densa and Eichhornia crassipes) (Brown and Michniuk 2007;Sousa et al 2009Sousa et al , 2010Yarrow et al 2009). Stands of E. densa alter the physical structure of Delta channels and support the colonization of non-native fishes such as sunfish (Centrarchidae), which are often able to outcompete or prey upon native fishes (See 2.30 Structure, below) Grimaldo et al 2004;Nobriga et al 2005;Nobriga and Feyrer 2007;Ferrari et al 2014).…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…in the rainy period) associated with chlorophyll-a high values (between 10.2 and 64.7 µg.L ), suggesting that this genus had been negatively affected by factors such as higher salt concentration mainly, higher total alkalinity values (<2.8 mEq.L -1 ). Yarrow et al (2009) describe E. densa as highly adaptable, being found throughout the world, except Antarctica, in a wide variety of physic-chemical sub-aquatic environments. Hauenstein and Ramírez (1986) found that E. densa tolerated salinities up to 5, growing naturally in the Valdivia river basin, but in laboratory salinity greater than 1 showed a slight inhibition of photosynthesis, growth and adventitious root production.…”
Section: Resultsmentioning
confidence: 99%